The Correlation Between Performances Among Lexical-Related Tasks and The Performance in The Sentence Construction Task - Azwar Abidin (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This study employed a quantitative correlational design to explore the correlation between the students' performances among lexical-related tasks and how these tasks affect the performance in a sentence construction task. Using IBM SPSS Statistics Version 22’s Pearson Partial Correlation Test, this study calculated participants' performance in primary lexical attributes by recognizing the following aspects of lexical knowledge: pronunciation patterns, morphological structures, syntactic properties, semantic characteristics such as abstract and interconnectedness, and a complete sentence construction in a strict naturalistic classroom setting. The test results showed that the participants made 297.05 seconds on average for 42 correct responses in Lexical Decision Task, 5.88 seconds per picture projected on the screen in Picture-Naming Task, 8.33 seconds for each word in Semantic Judgment Task, and 30.17 seconds on average to complete a sentence. These results concluded that the participants' performance in identifying strings of letters does not correlate significantly with their performance in understanding how a particular word functions grammatically within a sentence. In terms of the level of automaticity, the participants’ performance exceeded the average performance. The findings suggested that their performance in understanding primary lexical attributes in single lexicons does not facilitate their understanding of semantic characteristics. Henceforth, the students’ lexical knowledge does not yet construct an integrated linguistic representation in the target language acquisition. The study confirmed previous evidence that stated that a better performance in lexical-related tasks significantly impacted sentence processing and construction skill.